Analisis Ekonomi Kelembagaan Pengelolaan Kawasan Konservasi Perairan Teluk Depapre Di Kabupaten Jayapura - yudi wahyudin; Yunus P Paulangan; M Arsyad Al Amin; Taryono kodiran; Mahipal mahipal (Universitas Djuanda, 2018)
The objective goal of this research is to measure the institutional economic value of marine protected area management of Depapre Bay in Jayapura Regency. This institutional economic value can be measured by transaction cost analysis and ecosystem services valuation within techniques of project based cost approach (PBCA), benefit transfer (BTM) and basic payment ecosystem serives (BPES). The result shows that the transaction cost of marine protected area management amounted IDR 6.04-12.07 billion per year, meanwhile the potential benefit of ecosystem services of marine protected area management of Depapre Bay amounted IDR 1.62 trillion per year and the basic payment ecosystem services as an entrance fee to the marine conservation area amounted IDR 51,587.52 per people per trip. Key words: transaction cost, institutional economic, ecosystem services, entrance fee, PES